Effect of nitric oxide donors on blood pressure and pulse pressure in acute and subacute stroke - Gray, Laura J.; Sprigg, Nikola; Rashid, Parveen; Willmot, Mark; Bath, Philip M.W. (Elsevier, 2006)
High blood pressure (BP), pulse pressure (PP), and rate pressure product (RPP) areeach associated independently with a poor outcome in acute ischemic stroke. Whereas nitric oxide (NO) donors, such as glyceryl trinitrate (GTN), lower blood pressure in acute ischemic stroke, their effect on other hemodynamic measures is not known. We performed a systematic review of the effects of NO donors on systemic hemodynamic measures in patients with acute/subacute stroke. Randomized controlled trials were identified from searches of the Cochrane Library, Pubmed, and Embase. Information on hemodynamic measures, including systolic BP (SBP), diastolic BP (DBP), and heart rate, were assessed, and hemodynamic derivatives of these were calculated: PP (PP SBP DBP), mean arterial pressure (MAP DBP PP/3), mid blood pressure (MBP (SBP DBP)/2), pulse pressure index (PPI PP/MAP), and RPP (RPP SBP HR). The effect of treatment on hemodynamic measures was calculated as the weighted mean difference (WMD) between treated and control groups with adjustment for baseline. Results: Three trials involving 145 patients were identified; 93 patients received the NO donor, GTN, and 52 control. As compared with placebo, GTN significantly reduced SBP (WMD -9.80 mmHg, p< 0.001), DBP (WMD -4.43 mmHg, p<0.001), MAP (WMD -6.41 mmHg, p< 0.001), MBP (WMD -7.33 mmHg,p<0.001), PP (WMD -6.11 mmHg, p<0.001 ) and PPI (WMD -0.03, p=0.04 ). 3 GTN increased HR (WMD +3.87 bpm, p<0.001) and non-significantly lowered RPP (WMD -323 mmHg.bpm, p=0.14). Conclusion: The NO donor GTN reduces BP, PP and other derivatives in acute and subacute stroke whilst increasing heart rate.